2010
DOI: 10.1016/j.dld.2009.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and outcomes of drug-induced liver injury: Nimesulide as the first implicated medication

Abstract: a b s t r a c tBackground and aims: Drug-induced liver injury (DILI) is the most common cause of death from acute liver failure, and accounts for approximately 13% of cases of acute liver failure in the United States. The clinical presentation of DILI covers a wide spectrum, from asymptomatic liver test abnormalities to symptomatic acute liver disease, prolonged jaundice and disability, or overt acute or subacute liver failure. The aim of our study was to evaluate the number of DILI cases admitted to our Unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
1
24
0
2
Order By: Relevance
“…64 The toxicity of nimesulide to hepatocytes has been previously observed 65,66 which is attributed mainly to the nitro group in its structure. 67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 99%
“…64 The toxicity of nimesulide to hepatocytes has been previously observed 65,66 which is attributed mainly to the nitro group in its structure. 67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 99%
“…Nimesulide was the most commonly implicated NSAID, responsible for hepatocellular DILI in women and the cholestatic/mixed type in men [30,36]. Among antibiotics, we reported the impact of AMCinduced [37] and fluoroquinolone-induced [38] liver injury.…”
Section: Drugs Frequently Involved In Dilimentioning
confidence: 85%
“…Among these, NSAIDs are among the drugs most responsible for DILI 10 18–22. More specifically, nimesulide's safety was reviewed in 2007 and again in 2010 by the European Medicines Agency (EMEA), because of concerns with liver injury 18 23. The Agency's Committee for Medicinal Products for Human Use concluded that nimesulide was associated with an increased risk of liver toxicity compared with other anti-inflammatory treatments and that systemic nimesulide should not be used for long-term treatment 24…”
Section: Discussionmentioning
confidence: 99%